Ecological video monitoring of Marine Protected Areas by underwater cabled surveillance cameras. (September 2020) - Aguzzi, J.; Iveša, N.; Gelli, M.; Costa, C.; Gavrilovic, A.; Cukrov, N.; Cukrov, M.; Cukrov, Nu; Omanovic, D.; Štifanić, M.; Marini, S.; Piria, M.; et al.
Abstract: The ecological monitoring in Marine Protected Areas (MPAs) needs technological implementation to achieve the standard required for an advanced ecosystem management. This paper describes the use, and provide the initial results of a continuous time-lapse image monitoring system, cabled with underwater cameras located in a Natura 2000 site: Šibenik (Croatia, 43°44′9.85″N and 15°52′37.62″E, in the Adriatic Sea). The images of the mobile megafauna recorded during daylight hours from January 10 to the end of April 2018 were analysed. Overall, 13, 808 images were analysed and a total of 136, 195 animals were identified. A total of 16, 216 fish specimens, belonging to 35 species, were identified from 10, 026 images. These included 24 species of commercial interest, including the billfish Thunnus thynnus (Atlantic bluefin tuna) and animals of conservation interest such as the loggerhead turtle, Caretta caretta . The data collected in the time series showed an increase of fish biodiversity from winter to spring. Permutational Multivariate Analysis of Variance (PERMANOVA) revealed significant daily and seasonal changes in the assemblage structure. Canonical Analysis of Principal Coordinates and Principal Component Analysis indicated that fish assemblages were characterized by significant temporal changes at the mean Trophic Level and in the presence of different Functional Groups. Advantages and constraints of an image-based monitoring approach by cabled camera are discussed in relation the potential applications within the frame of international management programs, including the Marine Strategy Framework Directive (MSFD).